(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article deals with the problems and ways of teaching legal English, its main tasks and features. The circumstances of its origin, information about specific terminology related to the law are given as well.